Indian Business Sustainability in the Era of Globalization - Singh, Mitrabinda (Advances in management ( indexed in Cabell's Directory, RePEc and ERA ), 2010)
Indian Business is going through one of its golden times when many Indian companies are going global. Some of them have managed to be listed in top Stock Markets of the world and the year 2009 has record industrial growth after 20 years though many countries are struggling to come out of a big economic crisis. Globalization and boundary-less market had forced Indian Corporations to change their survival strategy. We have analysed one of such strategy which worked wonders for many Indian Business Sectors. This is nothing but the steps taken towards corporate environmental sustainability and disclosing the environmental performance to the customers and other stakeholders. Many of the past literatures on corporate sustainability never speak aloud of or, remain silent on Corporate Environmental sustainability.Some of them even argue that the natural stock/capital remains stable all the time. But, the ongoing changes and disasters like Tsunami, water and food shortage, climate change, inequalities and so on cannot be ignored. In fact, the figure shows the corporations realising the environmental issues in business and interested to contribute to save the nature so as to get the global competitiveness. India being the heavily industrialized country with an increasing rate of consumption is always blamed and warned about the disasters in many international forums. This paper provides an insight of Indian Business Sustainability in the era of globalization through an analysis of economic performance of 3 Indian corporations while they are investing towards environmental sustainability.